De novo transcriptome dataset of Stevia rebaudiana accession MS007 - Samsulrizal, Nurul Hidayah; Khadzran, Khairul S.; Shaarani, Siti Hajar Noor; Noh, Abdul Latif; Meenakshi Sundram, Tamil Chelvan; Naim, Mohd Azrul; Zainuddin, Zarina (Elsevier Inc., 2020)
Stevia rebaudiana (S. rebaudiana) is a herbaceous and perennial plant belonging to Asteraceae family. The genus stevia is well known as a natural producer of sweetener comprising non-caloric and non-carcinogenic steviol glycosides. In recent years, the capability in producing natural sweetner has increased the demand for S. rebaudiana as substitute of processed sugars. Flowering phase of S. rebaudiana has shown to affect the content of steviol glycosides in the leaves. Steviol glycosides level is the highest at the time of flower bud formation and lowest at time preceding and following flower bud formation. Therefore, sequencing and analysing the genes that are involved in flowering phase will provide platform for gene manipulation in increasing steviol glycosides content. The Stevia transcriptome data that include two stages of growth (before flowering and after flowering), were obtained using Illumina RNA-seq technology and can be accessed at NCBI Sequence Read Archive under Accession No. SRX6362785 and SRX6362784.